Semiconductor clusters: Synthetic precursors for colloidal quantum dots - Shin, Jibin; Choi, Mahnmin; Kim, Meeree; Jeong, Sohee (Frontiers in Nanotechnology, 2022)
Semiconductor clusters have been implicated as reaction intermediates between molecular precursors and colloidal quantum dots (CQDs). The success of isolation of semiconductor clusters have enabled detailed investigation of the atomic information of semiconductor clusters. The identification of atomic information has emerged as an important topic because knowledge of the structure-function relationship of intermediate clusters has been helpful to reveal the synthetic mechanism of CQDs. Recently, they have been utilized as the synthetic precursors for CQDs, which was not readily achieved using conventional molecular precursors. This mini review briefly introduces the current understanding of their atomic information such as the composition, structure, and surface. We then discuss advantages, limitations, and the perspective of semiconductor clusters as a precursor for synthesis of CQDs.